2005
DOI: 10.1051/parasite/2005122159
|View full text |Cite
|
Sign up to set email alerts
|

Strain characterization ofEchinococcus granulosusprotoscoleces of cattle origin using thein vitrovesicular development

Abstract: Summary :The aim of this work was to characterize the strain of protoscoleces of E. granulosus of cattle origin using the in vitro vesicular development. The in vitro development of these samples was compared to samples of sheep origin determined previously by genetic analyses as common sheep strain (G1). There were similarities between sheep and cattle samples not only in the time of microcysts formation, but also in the development process. Vesiculated protoscoleces and protoscoleces with posterior bladders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Evolution times and yield per tube of control cultures coincides with the previously reported results by our group [5] ( Table 1). The percentage of obtained cysts was around 1.6%.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Evolution times and yield per tube of control cultures coincides with the previously reported results by our group [5] ( Table 1). The percentage of obtained cysts was around 1.6%.…”
Section: Resultssupporting
confidence: 80%
“…granulosus protoscoleces behaviour in in vitro cultures has been quite well described previously [4][5][6][7]. A low percentage of protoscoleces develops into microcysts in in vitro systems supplemented with fetal calf serum, independently of their host origin (Table 1).…”
mentioning
confidence: 52%
“…Moreover, these authors have cultivated protoscoleces from sheep origin in 2005, and reported that there are no differences between the ovine and bovine during the development process and at the time of cysts' formation (Elissondo et al 2005).…”
Section: Discussionmentioning
confidence: 99%